Effects of intercropping with post-grafting generation of Cosmos sulphureus on cadmium accumulation of grape seedlings. Issue 2 (April 2020) - Wang, Xun; Wang, Yan; Wei, Xiaohan; Xiao, Yunying; Xu, Xiangting; Liao, Ming'an
Abstract: The pot experiment was carried out to study the effects of intercropping with post-grafting generation of Cosmos sulphureus on the cadmium accumulation of grape seedlings under cadmium stress. C. sulphureus which non-grafted (the offspring is named C. sulphureus S), self-rooted grafting by the same plant seedlings(the offspring is named C. sulphureus D), self-rooted grafting by two uniform plant seedlings (the offspring is named C. sulphureus T), and self-rooted graftingby two different development stages of plant seedlings (the offspring is named C. sulphureus Y). The results showed that intercropping significantly reduced the soil pH and increased the available cadmium content of the soil. Compared with grape monoculture, intercropping significantly reduced the cadmium content of grape seedlings roots. Among all treatments, grapeintercropping C. sulphureus Y maximized the biomass of grape seedlings and the cadmium accumulation of the post-grafting generation of C. sulphureus, and the cadmium content of the grape seedlings shoots was significantly lower than other treatments.